1998
DOI: 10.2135/cropsci1998.0011183x003800030010x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Genotype ✕ Environment Interaction in Wheat by Partial Least Squares Regression

Abstract: The partial least squares (PLS) regression method relates genotype ✕ environment interaction effects (GEI) as dependent variables (Y) to external environmental (or cultivar) variables as the explanatory variables (X) in one single estimation procedure. We applied PLS regression to two wheat data sets with the objective of determining the most relevant cultivar and environmental variables that explained grain yield GEI. One data set had two field experiments, one includingseven durum wheat (Triticum turgidum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 0 publications
0
70
0
3
Order By: Relevance
“…The analysis and interpretation of GEI range from simple analysis of variance to more speciWc analyses of genotype performance, from the univariate linear regression analysis of Finlay and Wilkinson (1963) and Eberhart and Russell (1966) or Perkins and Jinks (1968), to the multivariate AMMI (Zobel et al 1988), GGE biplot (Yan 2001) and PLSR (Partial Least Squares Regression) models (Vargas et al 1998). The commonly used linear regression analysis typically explains only a portion of the interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis and interpretation of GEI range from simple analysis of variance to more speciWc analyses of genotype performance, from the univariate linear regression analysis of Finlay and Wilkinson (1963) and Eberhart and Russell (1966) or Perkins and Jinks (1968), to the multivariate AMMI (Zobel et al 1988), GGE biplot (Yan 2001) and PLSR (Partial Least Squares Regression) models (Vargas et al 1998). The commonly used linear regression analysis typically explains only a portion of the interactions.…”
Section: Introductionmentioning
confidence: 99%
“…From the 1980's, the use of environmental variables and the prediction of their influence on the productivity of some species have been widely applied in the studies on the GxE interaction, and currently several authors have been inserting environmental information, whether as characterization factors and environmental stratification as covariates in the analysis models of GxE interaction (Haun, 1982;Denis, 1988;Van Eeuwijk et al, 1996;Vargas et al, 1998;Crossa et al, 1999;Van Eeuwijk et al, 2005;Voltas et al, 2005;Thomason and Phillips, 2006;Vargas et al, 2006;Boer et al, 2007;Ramburan et al, 2011;Heslot et al, 2014). Van Eeuwijk et al (1996), in a seminal study, summarizes some methods based on factor analysis for the insertion of information about environmental covariates for the explanation of the GxE interaction, and, according to the author, such models are just an extension of the most general case:…”
Section: Methodologies Using Covariatesmentioning
confidence: 99%
“…Where: H is the number of environmental covariates (Van Eeuwijk et al, 1996;Vargas et al, 1998;Crossa et al, 1999). Some studies have been using explanatory covariates in the most variable way possible.…”
Section: Methodologies Using Covariatesmentioning
confidence: 99%
“…More recent and comprehensive analysis (Reynolds et al 1998). Cluster analysis was based on cross-over interaction of genotypes as described by Vargas et al (1998) using CIMMYT international nursery yield data indicated that main genotype clusters correspond to three main types of environment, viz., temperate, continuous heat stress and terminal heat stress, and confirmed relative humidity as an important factor determining G×E within some of these clusters (Lillemo et al 2005).…”
Section: Abiotic-stress Environmentsmentioning
confidence: 99%